The Effect of Body Mass Index (BMI) And Age On Range Of Motion (ROM) of Articulatio Talocruralis in the Elderly in Wioi Village, Regency. Southeast Minahasa - Rumampuk, Jimmy Franky; Siada, Gracela Marchtica; Lintong, Fransiska; Danes, Vennetia Ryckerens; Moningka, Maya Esther Wullur; Pangemanan, Damayanti (Al Makki Health Informatics Journal, 2024)
Background: The ROM value of a joint indicates the flexibility of that joint. An increase in BMI value is one of the factors that can cause ROM values to decrease and will affect muscle and joint strength. Several studies have linked increased BMI with decreased ROM where obese populations have limited ROM compared to non-obese populations. Objective: This study aims to determine the relationship between body mass index (BMI) and range of motion (ROM) of articulatio talocruralis in the elderly in Wioi Village, Regency. Southeast Minahasa. Methods: This study is an analytic observational study with a cross sectional approach. The instruments used in this study were digital scales and stature meters to measure BMI, and goniometers to measure ROM. The research sample was selected using simple random sampling technique. Data were tested using binary logistic regression analysis method. Results: Of the 51 respondents studied, binary logistic regression analysis showed an effect of BMI on Dorsiflexion (p = 0.023, β = -0.197) and Plantarflexion (p = 0.014, β = -0.254), but no effect of age on Dorsiflexion (p = 0.635, β = -0.022) and Plantarflexion (p = 0.173, β = -0.069). Conclusion: Body mass index (BMI) affects the range of motion (ROM) of articulatio talocruralis, but age does not affect the range of motion (ROM) of articulatio talocruralis in the elderly in Wioi Village, Regency. Southeast Minahasa.